Proceedings of ISCAS'95 - International Symposium on Circuits and Systems
DOI: 10.1109/iscas.1995.520379
|View full text |Cite
|
Sign up to set email alerts
|

A preconditioned iterative solver for dynamic simulation of power systems

Abstract: In this paper the General Minimal Residual (GMRES) is applied for the dynamic simulation of a power system. GMRES is an iterative method belonging to the class of conjugate gradient methods which is well suited for parallelisation and easily programmable. When used with an appropriate preconditioner speed ups are considerable compared to the LU factorization method. Results on a workstation as well as a supercomputer are presented for a 10 machine 39 bus system to illustrate the speed ups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 12 publications
0
7
0
4
Order By: Relevance
“…From the electrical power modeling perspective, there has been some work on using iterative methods for solving the complex-symmetric systems arising in electrical power modeling; see, e.g., [4], [7], [15], [17]. However, these methods have not addressed the ill-conditioning associated with faults in the electrical power system.…”
Section: Ac Power Network Consider the Linear Systemmentioning
confidence: 99%
“…From the electrical power modeling perspective, there has been some work on using iterative methods for solving the complex-symmetric systems arising in electrical power modeling; see, e.g., [4], [7], [15], [17]. However, these methods have not addressed the ill-conditioning associated with faults in the electrical power system.…”
Section: Ac Power Network Consider the Linear Systemmentioning
confidence: 99%
“…in small signal stability analysis [16]. Pai et al used another iterative method (GMRES), which is applicable to both symmetric and unsymmetric matrices, for the dynamic simulation of power systems [19].…”
Section: Initializementioning
confidence: 99%
“…A literature review on iterative methods and power systems problems revealed a majority of steady-state studies [3][4][5][6][7][8][9][10][11][12][13][14][15]. Despite time domain simulation be an important tool for dynamic assessment of power systems [16][17][18], the application of iterative methods have been focused only on the solution of short-term phenomena (transient stability) through implicit integration methods with fixed step sizes, taking advantage of parallel or distributed computing [3,4,13,14].…”
Section: Introductionmentioning
confidence: 99%